Effect Of Use Of Aromatherapy And Murotal Therapy In Mother's Parting With Anxiety - Maya Herlina, Siskha; Ulya, Yadul; Yunika, Regina Pricilia (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Anxiety is a feeling of fear that is unclear and not supported by the situation. Individuals who feel anxious will feel uncomfortable or afraid, but do not know the reason why this condition occurs. Anxiety has no clear, identifiable stimulus. Murotal therapy can speed up healing and reduce anxiety, listening to the holy verses of the Al-qur’an has a significant influence in reducing tension in the reflective nerves. The recommended aroma for mediating anxiety is aromatherapy based on lemon essential oil (Citrus limon) Objective: To determine the effectiveness of Murottal therapy on the level of anxiety of women giving birthMethod: This type of research uses qualitative research, with a cross-sectional approach. The sample in this study was 30 mothers in the first stage of labor. This research uses chi square data analysisResults: Based on the frequency distribution of the influence of the use of aromatherapy and murrotal therapy on mothers giving birth with anxiety, it shows that there is an influence of the use of aromatherapy and murrotal therapy on mothers giving birth with anxiety.Conclusion: Based on the research results, murottal therapy on maternal anxiety levels before giving birth is effective.Suggestion: Murottal therapy has good effectiveness, it is hoped that this therapy can relieve and be a solution to the anxiety experienced by mothers during pregnancy, childbirth and postpartum. Keywords: Anxiety, Murottal Al-Qur'an, Aromateraphy